Towards a redefinition on the role of library student assistants in the provision of library service - Humarang, Lora C. (2003)
The UP Diliman libraries serve a wide variety of clients including UP students, UP faculty, UP employees and other outside researchers. In order to accommodate this large number of clients, the administration set up a Library Student Assistantship Program which will hopefully ensure an effective and efficient library service. Although Library Student Assistants in the provision of library service is still indefinite. So, what exactly is the role of Library Student Assistants in the provision of Library Service?